PENGGUNAAN NATRIUM SIKLAMAT PADA ES LILIN BERDASARKAN PENGETAHUAN DAN SIKAP PRODUSEN DI KELURAHAN SRONDOL WETAN DAN PEDALANGAN KOTA SEMARANG (Natrium Cyclamate on the Ice Candle Based on the Producer’s Knowledge in Srondol Wetan and Pedalangan, Semarang) - Retno Purwaningsih; Rahayu Astuti; Trixie Salawati (Jurnal Pangan dan Gizi, 2010)
Sodium Cyclamate is an artificial sweetener that is often used. Sodium cyclamate could be carcinogenic. The use of sodium cyclamate in Indonesia regulated in a No 722/MenKes/Per/IX/88 Permenkes RI and RI Permenkes no.208/MenKes/Per/IV/85 about usage limits for each food product. The data of BBPOM Semarang in 2007 found sodium cyclamate in food snacks (student of  primary school) including ice candle. The purpose of this study is to measure the use of sodium cyclamate at ice candle producers based on knowledge and attitudes about the content of sodium cyclamate.. This research is explanatory with the survey method. The population is all the ice candle producers in  Srondol Wetan and Pedalangan, as many as 25 producers. Samples were tested in the laboratory ice candle BB POM Semarang. Data analysis using Spearman rank correlation test. The results showed the level of knowledge of respondents 'good' by 16.0%, the category of "enough" of 52.0% and "less" of 32.0%. Respondents who have the attitude of "support" of 64.0% and 36.0% "no support". The content of sodium cyclamate in 17 samples (68.0%) positive and 8 samples (32.0%) negative. Positive samples containing sodium cyclamate, there were 14 samples (82.35%) that concentration is still below the maximum limit and 3 samples (17.65%) which exceeds the maximum limit. There is a relationship between knowledge and attitude of the ice candle producers with the use of sodium cyclamate in  Srondol Wetan and Pedalangan of Semarang. Key words: Sodium Cyclamate, Knowledge, Attitude, Prodecers of ice candle